The Informational Efficiency of the Corporate Bond Market: An Intraday Analysis - Hotchkiss, Edith S.; Ronen, Tavy (Review of Financial Studies, 2002)
Using a unique dataset based on daily and hourly high-yield bond transaction prices, we find the informational efficiency of corporate bond prices is similar to that of the underlying stocks. We find that stocks do not lead bonds in reflecting firm-specific information. We further examine price behavior around earnings news and find that information is quickly incorporated into both bond and stock prices, even at short return horizons. Finally, we find that measures of market quality are no poorer for the bonds in our sample than for the underlying stocks.